2013
DOI: 10.1016/j.celrep.2013.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Insulin/IGF-1 Signaling Regulates Proteasome Activity through the Deubiquitinating Enzyme UBH-4

Abstract: The proteasome plays an important role in proteostasis by carrying out controlled protein degradation in the cell. Impairments in proteasome function are associated with severe and often age-related diseases. Here, we have characterized a molecular mechanism linking insulin/IGF-1 signaling (IIS) to proteasome activity. We show that decreased IIS, which promotes proteostasis and longevity, increases proteasome activity through the FOXO transcription factor DAF-16 in C. elegans. Furthermore, we reveal that DAF-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(105 citation statements)
references
References 72 publications
5
98
2
Order By: Relevance
“…Furthermore, the possibility of high internal recycling is supported by the observation that autophagic activity in C elegans daf-2 mutants is a prerequisite for their longevity (16,17,56). Also, increased proteasomal activity may underlie an elevated free aminoacid pool in daf-2 animals (57). However, we found that RNAi inhibition of proteasomal subunits did not lower the elevated 35 S sTCA signal in the daf-2 mutants (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the possibility of high internal recycling is supported by the observation that autophagic activity in C elegans daf-2 mutants is a prerequisite for their longevity (16,17,56). Also, increased proteasomal activity may underlie an elevated free aminoacid pool in daf-2 animals (57). However, we found that RNAi inhibition of proteasomal subunits did not lower the elevated 35 S sTCA signal in the daf-2 mutants (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Uch37 has been implicated in DNA replication and cell cycle [141], TGF-β signaling [142145], WNT signaling via Tcf7 [146], longevity [147], cell migration and invasion [148], and the reversal of ubiquitination of proteasome subunits [138]. It is difficult to resolve common themes from the physiological studies reported to date.…”
Section: Physiological Functionmentioning
confidence: 99%
“…Decreased IIS induces proteasome activity in worms through DAF-16 transcriptional repression of the proteasome-associated deubiquitinating enzyme ubh-4 (ref. 159). UCHL5, the human orthologue of ubh-4, increases degradation of toxic proteins in mammalian cells 159 .…”
Section: Loss Of Clearance Mechanisms As a Determinant Of Ageingmentioning
confidence: 99%
“…159). UCHL5, the human orthologue of ubh-4, increases degradation of toxic proteins in mammalian cells 159 . Autophagy also contributes to the longevity phenotype of reduced IIS C. elegans mutants.…”
Section: Loss Of Clearance Mechanisms As a Determinant Of Ageingmentioning
confidence: 99%